Effects of one-time and two-time intra-articular injection of hyaluronic acid sodium salt after joint surgery in dogs - Nganvongpanit K. (2014)
Thirty-one dogs with patellar luxation (grades 2 and 3) were categorized into three groups. Group 1 (G.1; n = 12) had sodium hyaluronate (SHA) intra-articularly injected into the stifle joint that received surgery. Group 2 (G.2; n = 10) received SHA twice: first after surgery and then 1 week later. Group 3 (G.3; n = 9) served as a control, without injection. Blood was collected before injection and then once a week for 4 weeks after injection for evaluation of chondroitin sulfate (CS-WF6) and hyaluronan (HA). The results revealed significantly (p < 0.05) improved clinical scores by the end of week 4 in G.1 and G.2 relative to G.3; however, there was no significant difference between G.1 and G.2. There was a significant decrease (p < 0.05) in serum CS-WF6 levels beginning at week 2 in G.1 and G.2. At weeks 3 and 4, serum HA in G.1 and G.2 differed from that in G.3 (p < 0.05). No significant difference (p > 0.05) was observed in serum biomarkers between G.1 and G.2. In conclusion, intra-articular injection with SHA after joint surgery may improve homeostasis of the joint, retarding the process of OA. © 2013 The Korean Society of Veterinary Science.